Biologic Therapy and Severe Asthma in Children - Daniele Russo; Paola Di Filippo; Marina Attanasi; Mauro Lizzi; Sabrina Di Pillo; Francesco Chiarelli (Biomedicines, 2021)
Severe asthma is a heterogeneous, complex and chronic disease widespread in the pediatric population. According to the recent findings about the different endotypes of asthma in children, each one characterized by specific intracellular molecular pathways, several innovative biologic therapies have been developed. Due to their precise ability to target specific inflammatory type 2 mediators, biologics have revolutionized the care of chronic allergic diseases in the pediatric and adult population. In this review, we aim to provide the latest evidence about the use, indications, efficacy and safety of biologic therapies to treat severe asthma in children and adolescents.